Leonard F. Cushing papers - Cushing, Leonard F., 1901-1962.
Correspondence, blueprints, specifications, newspaper clippings, and photographs relating to the restoration of the USF Constitution and the USF Constellation. Includes material concerning the histories of the two frigates and the controversy over the authenticity of the Constellation. Correspondents include Robert H. Burgess, Garnett Laidlaw Eskew, Samuel N. Friedel, W.E. Howard, Jr., Fred C. Kilguss, Burton M. Parks, Leverett Saltonstall, Charles Scarlett, Jr., Russell M. Stephens, Donald Stewart, and J.R. Whittemore.
Naval architect.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Burgess, Robert H. -- Correspondence; Eskew, Garnett Laidlaw, -- 1894- -- Correspondence; Friedel, Samuel N. -- 1898-1979 -- Correspondence; Howard, W. E. -- Jr. -- Correspondence; Kilguss, Fred C. -- Correspondence; Parks, Burton M. -- Correspondence; Saltonstall, Leverett, -- 1892-1979 -- Correspondence; Scarlett, Charles -- Correspondence; Stephens, Russell M. -- Correspondence; Stewart, Donald -- Correspondence; Whittemore, J. R. -- Correspondence; United States. -- Navy; Constitution (Frigate); Constellation (Frigate); Naval architecture; Shipbuilding; Warships; Naval architects